2019
DOI: 10.1002/nur.21978
|View full text |Cite
|
Sign up to set email alerts
|

Well siblings of children with chronic illness: A synthesis research study

Abstract: Well siblings of chronically ill children experience family disruptions that profoundly affect them. Previous research focusing on well siblings’ experiences has often produced inconsistent findings, likely the result of varying study designs and samples. The purposes of this synthesis research study were twofold: (a) to assess the applicability of existing grounded theory of sibling response to a child's cancer to a wider range of childhood conditions; and (b) to refine the existing theory to reflect the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 86 publications
3
16
0
19
Order By: Relevance
“…We found that adolescents and young adult siblings exhibited three dynamic psychosocial strategies to manage their experience over time: avoiding emotional awareness, normalizing their life experiences and approaching their siblings with a chronic health condition through active involvement in his or her care. Our findings are consistent with a recent synthesis study (Havill et al, 2019), which reported that finding a balance was a common theme the brother or sister of a child with a chronic health condition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that adolescents and young adult siblings exhibited three dynamic psychosocial strategies to manage their experience over time: avoiding emotional awareness, normalizing their life experiences and approaching their siblings with a chronic health condition through active involvement in his or her care. Our findings are consistent with a recent synthesis study (Havill et al, 2019), which reported that finding a balance was a common theme the brother or sister of a child with a chronic health condition.…”
Section: Discussionsupporting
confidence: 93%
“…Although siblings of a child with CF and their peers reported similar quality of life, further research studies are needed to identify less obvious disease‐related issues, such as ‘hidden stress’ and ‘sense of control’ (Havermans et al, 2015). Qualitative research has been used to identify the siblings' perspectives of their experiences as well as perspectives of parents and the ill child, including the patterns of adapting to changes in personal and family life (Havill et al, 2019). Many qualitative studies previously published were conducted by proxy and not from the sibling's perspective, and consequently, the distinct opinions and views of healthy siblings were overlooked (Deavin et al, 2018; Knecht et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Siblings have a strong desire to know and understand their ill sibling's condition. Moreover, information helps siblings' engagement with family and familiarity with hospital environments ( 26 ). Moreover, interaction with medical care, system, and staff influence siblings ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the result indicated that most facilities did not explain the medical and living conditions of the admitted child directly to their siblings. In contrast, information is often directly provided to siblings by their parents ( 26 ). Additionally, more than half of the participants in this study answered that they intentionally bring up siblings in conversation with their parents to provide indirect siblings support.…”
Section: Discussionmentioning
confidence: 99%
“…Esto, debido a que la mayoría de artículos revisados se enfocaron en un corte transversal durante este proceso, lo cual muestra cómo se encuentran en ese momento, pero ignora los cambios a medida que pasa el tiempo. Para encontrar esta información, son necesarios artículos de corte longitudinal que lleven un registro de los cambios en el tiempo que ha transcurrido durante el proceso de diagnóstico y tratamiento [50].…”
Section: Discussionunclassified